Proteção das florestas no direito internacional: considerações sobre o reconhecimento e implementação de obrigações vinculantes relacionadas aos objetivos globais sobre florestas - Souza, Luciano Pereira de (2017)
In the view of the failure to meet the Global Objectives on Forests set forth by means of a soft law instrument approved within the United Nations, notably the failure to achieve zero deforestation in 2015, the scope of this research was to study the protection of forests under International Environmental Law, addressing as central problem the legally binding nature or not of the commitments related to the forest sector that were unilaterally established by the States in their contributions to reduce greenhouse gas emissions presented under the Paris Agreement, known as NDCs. The research adopts Norberto Bobbio's proposal that recognizes a promotional function of the Law, when it uses legal mechanisms of incentive as prize sanctions to reflect on the possibility that obligations of forest protection may acquire legally binding status, but in a form different from the traditional responsibility based on the imposition of punitive sanctions. Through this alternative pathway, the principle of good faith guiding international law of treatise, also the principle of international cooperation and the principle of common but differentiated responsibilities in the equitable distribution of burdens and duties among states could be evoked for solving common problems of Mankind, such as the preservation and sustainable use of forests, by means of adoption of governance processes. Starting from the norm of customary International Law ruling that States have sovereignty over natural resources in their territories, including forests, but cannot make use of nor let these resources be used to the detriment of other states and of humanity itself, it is possible to establish legal expectations of State behavior in relation to forests based on soft law commitments assumed collectively or unilaterally by the States. Using bibliographical and documentary research, this study adopted a dialectical approach when inserting its object in a totality undergoing a process of transformation powered by permanent tensions.The first part of this research described an overviewed forest protection on the international global community, within and beyond international regimes, with greater attention to the climate change regime, demonstrating the existence of a global forest protection´s culture (opinio iuris et necessitatis), as well as an emerging repeated practice of conservation and sustainable use of forests. The second part of the research reflected on the concept of forests, based on the notion of geographic object found in Milton Santos and it was tried to provide a brief overview of the forest cover on the planet and especially of the Amazon Forest, over the last 25 years, revealing a scenario of permanent forest loss. The third part of the study sought to determine the legal status of forestry obligations, under ethical, scientific and legal basis, which included Human Rights and ius cogens, soft law and its obligations, international cooperation and sovereignty over natural resources, closing with the study of the NDCs as autonomous unilateral acts and their status as source of Law and obligations under International Law, seeking a response to whether the commitments, objectives and forest goals inserted in these unilateral acts under Paris Agreement are binding or not.